Business Cycle Models with Endogenous Technology - Stadler, George W. (American Economic Review, 1990)
This paper compares real and monetary business cycle models with and without endogenous technical change. If technology is endogenous, the properties of these models change significantly. In particular, both real and monetary models yield very similar output processes if growth is endogenous, and changes in aggregate demand can result in permanent changes in productivity, employment, and output. The effect of depreciation of technology is examined, and the pattern of real wage movements over the cycle when money wages are fixed, but technology is changing, is briefly considered. Copyright 1990 by American Economic Association.